Does hedging tell the full story? Reconciling differences in US aggregate and industry-level exchange rate risk premia - Bill B. Francis; Iftekhar Hasan; Delroy M. Hunter (Bank of Finland, 2008)
While the importance of currency movements to industry competitiveness is theoretically well established, there is little evidence that currency risk impacts US industries. Applying a conditional asset-pricing model to 36 US industries, we find that all industries have a significant currency premium that adds about 2.47 percentage points to the cost of equity and accounts for approximately 11.7% of the absolute value of total risk premia. Cross-industry variation in the currency premium is explained by foreign income, industry competitiveness, leverage, liquidity and other industry characteristics, while its time variation is explained by US aggregate foreign trade, monetary policy, growth opportunities and other macro variables. The results indicate that methodological weakness, not hedging, explains the insignificant industry currency risk premium found in previous work, thus resolving the conundrum that the currency risk premium is important at the aggregate stock market level, but not at industry level
URN:NBN:fi:bof-20140807232
Keywords: 330